Increasing Children's Creativity Using Drawing Techniques with Numbers on the Results of Elementary School Students - Rizka Agunging Azri; Sudarmin Sudarmin; Sri Wardani; Deni Setiawan (Universitas Negeri Semarang, 2023)
This study was initiated because of the lack of student creativity in producing drawings. In addition, the work produced by students also still has similarities between one another. So students need to be invited to develop their imagination in drawing by using ways that can increase creativity, one of which is by using drawing techniques with numbers. This study aims to explore and describe the results of students' drawing using the technique of drawing by numbers in elementary school. This type of research is descriptive qualitative research. The data in this study were obtained through observation, interviews and documentation. The population in this study were grade II students at SDN 1 Klopoduwur . The instruments used in this study, namely observation, interviews, and documentation instruments as well as student work. The results showed that by using the drawing technique with numbers, students experienced an increase in terms of creativity. It can be seen from the results of the drawings each student is able to draw with numbers 0 to 9 into interesting drawings and the resulting drawings are also more varied.